Diverging Trends in Single-Mother Poverty across Germany, Sweden, and the United Kingdom: Toward a Comprehensive Explanatory Framework. (6th December 2021) - Zagel, Hannah; Hübgen, Sabine; Nieuwenhuis, Rense
Abstract: To explain single-mother poverty, existing research has either emphasized individualistic, or contextual explanations. Building on the prevalences and penalties framework (Brady et al. 2017 ), we advance the literature on single-mother poverty in three aspects: First, we extend the framework to incorporate heterogeneity among single mothers across countries and over time. Second, we apply this extended framework to Germany, the United Kingdom and Sweden, whose trends in single-mother poverty (1990–2014) challenge ideal-typical examples of welfare state regimes. Third, using decomposition analyses, we demonstrate variation across countries in the relative importance of prevalences and penalties to explain time trends in single-mother poverty. Our findings support critiques of static welfare regime typologies, which are unable to account for policy change and poverty trends of single mothers. We conclude that we need to understand the combinations of changes in single mothers' social compositions and social policy contexts, if we want to explain time trends in single-mother poverty.